Sosialisasi dan Edukasi Literasi Keuangan Untuk Warga ‘Aisyiyah Kabupaten Sukoharjo Guna Mengurangi Perilaku Konsumtif Pada Remaja dan Anak-Anak - Dhany Efita Sari (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
People who are financially literate are people who have the attitudes, skills and knowledge to manage one's finances to meet financial goals that help achieve life goals. In fact, the majority of the citizens of 'Aisyiyah in Sukoharjo Regency have children who are extravagant or consumptive, like to follow trends, and are less able to prioritize their needs than their desires so that they cannot understand and apply financial literacy in life daily. Based on the conditions experienced by residents of  Aisyiyah, Sukoharjo Regency, there is a need for financial education and outreach for adults to be able to be applied to their children. The education and socialization program provided is expected to reduce consumptive behavior in children and provide benefits to the residents of the community ‘Aisyiyah Sukoharjo Regency to develop knowledge and understanding of financial literacy education and the ability to manage finances well.